Survey of Ethnoveterinary Medicines Used to Treat Livestock Diseases in Omusati and Kunene Regions of Namibia - Eiki, Ndahambelela; Maake, Matome; Lebelo, Sogolo; Sakong, Bellonah; Sebola, Nthabiseng; Mabelebele, Monnye (Frontiers in Veterinary Science, 2022)
The aim of this study was to find, evaluate, and document ethnoveterinary medications used to treat livestock ailments in Namibia's Omusati and Kunene regions. A semi-structured questionnaire was used to interview a total of 100 people. The results of the survey will be useful in creating the groundwork for future scientific research and validation. There were 15 veterinary medicinal plant species identified, which were divided into 10 families. The only types of growth that were utilized were trees, herbs, and bushes. Leaves (71%) were the most widely used plant parts for ethnoveterinary medicine (EVM), followed by bark (14%), stem (8%), and root (7%). Fresh components were frequently preferred in medical compositions. Oral administration was the most common (42.76%), followed by cutaneous (topical) administration (36.18%). Indigenous knowledge was largely passed down through the generations by word of mouth, indicating that it was vulnerable to fragmentation and loss. EVMs were crushed, soaked in water, and administered orally or topically. Farmers who were older had greater EVM knowledge than those who were younger. Ziziphus mucronate, Combretum collinum, and Colophospermum mopane were used in the treatment of diarrhea. Z. mucronate was also used in the treatment of mastitis. Skin infections were treated using Aloe esculenta and Salvadora persica. Ximenia americana and C. imberbe were used to treat eye infections in cattle, goats, and sheep. Retained placentas were treated using Acacia nilotica, A. erioloba, and Grewia flavescens. Roots from Fockea angustifolia were used in treating anthrax. A. esculenta Leach placed best with a fidelity level (FL) value of 90%, followed by A. littoralis Baker in second place (56%), and Combretum collinum Fresen in third place (54%). The majority of EVM recipes took 2–3 days to recover. More research is needed to determine the minimum inhibitory concentrations, biological activities, and toxicities, as well as characterize the chemical components of the plants and determine whether there is a plausible mechanism by which plant chemicals or possible physiological effects could achieve the results described by the respondents.